Otto Koenigsberger's Architectural Photographic Archive in India (1939–1951). (2nd October 2018) - Baweja, Vandana
Abstract : Otto H. Koenigsberger (1908–1999), a German émigré architect who worked as the state architect in princely Mysore in British India in the 1940s, left a rich collection of photographs of his architecture and planning projects, which now constitute his archive at the Architectural Association Archives in London. This article examines his photographic archive produced between 1939 and 1951 with two objectives. The first is to trace the aesthetic genealogies of the diverse photographic modes used in Koenigsberger's architectural projects; the second is to establish the importance of Koenigsberger's architectural photographic archive as a historic artifact in Mysorean architectural histories. I argue that Koenigsberger used photography to represent the ideological tension between modernist and revivalist architectures. In addition, in theorizing the use of photographic modes in relationship to Koenigsberger's architecture, I build upon Maria Antonella Pelizzari and Paolo Scrivano's argument that the relationship between the production of architectural photographs and architecture illuminates the underlying ideological constructs that inform both practices. Ultimately, I aim to demonstrate how Koenigsberger's photographic archive represents a rift in a seamless history of revivalist architecture in princely Mysore.